indonesia - Cahyani, Nadilah Dwi (Maliki Interdisciplinary Journal, 2025)
Behind the success of students in achieving various accomplishments lies the dedication of honorary teachers who guide them with great commitment. As of 2023, there are approximately 731,524 honorary teachers spread across different educational levels in Indonesia. These teachers play a crucial role in the national education system, particularly by filling the gap in teaching staff in underserved and remote areas. However, despite their vital contributions, many honorary teachers face inequality, especially in terms of recognition and compensation. The lack of appreciation and inadequate incentives may negatively affect their motivation, performance, and the quality of education delivered. This situation poses a serious challenge to efforts aimed at improving the overall quality of education. Therefore, concrete actions are needed from both the government and the private sector to enhance the recognition and appreciation of honorary teachers. Such appreciation should not only be financial but also include professional acknowledgment, career development opportunities, and legal and social protection. Improving the status and welfare of honorary teachers will positively impact the national education system, creating a fairer, more professional, and sustainable educational environment.